Eleventh Five Year Plan (2007-2012) Volume-II Social Sector Services - Planning Commission (Planning Commission, 2007)
The role of education in facilitating social and economic progress is well recognized. It opens up opportunities leading to both individual and group entitlements. Education in its broadest sense of development of youth is the most crucial input for empowering people with skills and knowledge and giving them access to productive employment in future.
Government of India
Government of India